2021
DOI: 10.1101/2021.05.14.444129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Yin Yang 1 sets up the stage for cerebellar astrocyte maturation

Abstract: Diverse subpopulations of astrocytes tile different brain regions to accommodate local requirements of neurons and associated neuronal circuits. Nevertheless, molecular mechanisms governing astrocyte diversity remain mostly unknown. We explored the role of a zinc finger transcription factor Yin Yang 1 (YY1) that is expressed in astrocytes. We found that specific deletion of YY1 from astrocytes causes severe motor deficits in mice, induces Bergmann gliosis, and results in simultaneous loss of GFAP expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 76 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Studies have also shown that YY1 deletion in the mid‐hindbrain region produced abnormalities in brain development by disrupting cell cycle, Wnt signaling, and p53‐induced cell death of neuroepithelial cells (Dong & Kwan, 2020). Recent studies have also shown that GFAP‐specific YY1 deletion during end‐stage embryonic development caused phenotype abnormalities and severe motor deficits, suggesting a linkage to impaired cerebellar astrocyte maturation (Mockenhaupt et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have also shown that YY1 deletion in the mid‐hindbrain region produced abnormalities in brain development by disrupting cell cycle, Wnt signaling, and p53‐induced cell death of neuroepithelial cells (Dong & Kwan, 2020). Recent studies have also shown that GFAP‐specific YY1 deletion during end‐stage embryonic development caused phenotype abnormalities and severe motor deficits, suggesting a linkage to impaired cerebellar astrocyte maturation (Mockenhaupt et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Increased expression levels of multiple chemokines including Cxcl10 may facilitate intercellular communication between glia and neurons (Banisadr et al, 2005). CXCL10 was highly upregulated in both astrocytes and microglia of all brain regions in astrocytic YY1 cKO mice as well as YY1-knockdown astrocytic cultures (Figure 10), suggesting that astrocytes are responsible for the inflammatory phenotype in the brain (Mockenhaupt et al, 2021), at least in part by YY1 deficiency in astrocytes. CXCL10 upregulation is linked to neurodegenerative diseases (Xia et al, 2000) and induces neuronal injury by dysregulating mitochondrial function (Sui et al, 2006) and promoting a proinflammatory environment (Jiang, Huang, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations